THE INFLUENCE OF MARXISM THOUGHT THAT ARE CONTAINED IN â€œLES JUSTESâ€ DRAMA SCRIPT BY ALBERT CAMUS - Hadiansyah Yanuar Rizqi Aktsar (Proceeding IICACS, 2019)
Karl Marx is told as an inspirator with great ideas. Marx claimed that there are laws of social development as well as the opening of secrets about a capitalist economy. Indeed at the level of theory, communism has a noble purpose but in practice many bad things happened. Lenin was the first thinker of marxism to bring marxism to actual practice, a revolution run by it to realize the utopia of Marxism in which Marxism in the hands of Lenin is not a philosophy of ordinary economics. The Just Assassins (original French title: â€•Les Justesâ€–, a more literal translation is The Just or The Righteous) is a drama script in 1949 by French writer and philosopher Albert Camus. The drama is based on the true story of a group of Russian Socialist-Revolutionaries who killed Grand Duke Sergei Alexandrovich in 1905, and explored the moral issues associated with murder and terrorism. In the drama, all but one (Stepan) of